MEASURING ADMINISTRATIVE SKILLS IN PUBLIC TERTIARY INSTITUTIONS IN CROSS RIVER STATE: IMPLICATION FOR EFFECTIVE GOVERNANCE AND SERVICE DELIVERY (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Effective governance and service delivery in public tertiary institutions hinge on robust administrative skills, yet their measurement remains underexplored in developing contexts like Nigeria. This study investigates administrative skills among administrators in public tertiary institutions in Cross River State, Nigeria, and their implications for governance and service delivery. Utilizing a mixed-methods approach, primary data were collected through surveys and interviews with 200 administrators and 50 academic staff across three institutions. Findings reveal that while administrators exhibit moderate proficiency in communication and financial management (mean scores: 3.8 and 3.6), skills in ICT and strategic planning lag (mean scores: 2.9 and 3.1). Demographic analysis shows a predominantly male (65%) and middle-aged (35–50 years) participant pool, with varying experience levels. Key challenges include inadequate training and outdated infrastructure, hindering effective service delivery. The study highlight that strong administrative skills correlate with improved governance outcomes, such as timely service delivery and stakeholder satisfaction. Recommendations include mandatory ICT training, investment in digital infrastructure, and policy reforms to enhance administrative capacity. This research provides a framework for assessing and strengthening administrative competencies, positioning Cross River State’s institutions as models for effective governance in Nigeria’s higher education sector.